1979
DOI: 10.1254/jjp.29.349
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory alpha-adrenergic action of phenylephrine in guinea pig taenia caecum

Abstract: Abstract-Phenylephrine, a selective a-adrenergic stimulant, caused a maximal re laxation of the taenia from guinea pig caecum in the concentration of 10-6 g/ml. Phenylephrine in this concentration did not influence intracellular cyclic AMP and cyclic GMP levels. Although phenylephrine abolished the spontaneous spike discharge, no change was detected in "Ca-uptake and "Ca-efflux on the tissue level after phenyl ephrine. Ca-uptake and Ca-release on the subcellular level were also not influenced by phenylephrine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…a-I-Adrenoceptor stimulation caused a net loss of potassium from isolated guinea-pig hepatocytes, and a net uptake of potassium into rat hepatocytes (Burgess et al 1981), and a transient net calcium efflux from perfused rat liver (Reinhart et al 1982). Iwayama et al (1979) found no detectable change in 45Ca-uptake or efflux in guinea pig taenia caecum after a-adrenergic stimulation. In contrast, they found that phenylephrine increased 42Kefflux.…”
mentioning
confidence: 69%
“…a-I-Adrenoceptor stimulation caused a net loss of potassium from isolated guinea-pig hepatocytes, and a net uptake of potassium into rat hepatocytes (Burgess et al 1981), and a transient net calcium efflux from perfused rat liver (Reinhart et al 1982). Iwayama et al (1979) found no detectable change in 45Ca-uptake or efflux in guinea pig taenia caecum after a-adrenergic stimulation. In contrast, they found that phenylephrine increased 42Kefflux.…”
mentioning
confidence: 69%
“…In one study rat hepatocytes had a net uptake of potassium in contrast to isolated guinea-pig hepatocytes which had a net potassium loss (Burgess et al 1981). In guinea pig teania caecum (Iwayama et al 1979) and in rat parotid gland tissue (It0 et al 1982), increased potassium efflux was found to be an a-adrenoceptor mediated effect.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, phenyle phrine exerted no effect on the 45Ca-efflux from the partly depolarized taenia coli of guinea pigs, indicating that the a-agonist induced relaxation of the smooth muscle is not related to the acceleration of Ca-efflux. Iwayama et al (9) have studied the effect of phenylephrine on the cellular calcium movements in the polarized taenia coli, demonstrating that phenylephrine does not inhibit the cellular 45Ca-uptake. In addition, they observed that phenylephrine caused the hyperpolarization in the polarized taenia coli smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the relaxation of the taenia coli of guinea pigs in response to a-agonists is related to the acceleration of K+ flux (8,9,22), while the role of Na+ on the a-adrenergic action remains nuclear. The present results demonstrated that the relaxant action of phenylephrine was completely lost in the Na-free solution in which Na+ was replaced by substitutes such as sucrose, choline and Tris, but restored in proportion to the amount of Na+ readded to the Na-free solution.…”
Section: Discussionmentioning
confidence: 99%